COVID‐19: not just an acute illness. Issue 6 (26th November 2020) - Miller, Alastair
Abstract : Some people with COVID‐19 will need support for physical, emotional and mental symptoms long after they have recovered from the acute phase of the infection. Many of those with so‐called 'long Covid' are likely to have a post‐viral condition very similar to chronic fatigue syndrome/myalgic encephalomyelitis for which management guidelines and a network of NHS clinics already exist.